Successful intubation using video laryngoscope in a child with CHARGE syndrome - A case report - Kim, Jeongho; Hong, Jeong In; Chae, Kyoung-lin; Yoon, Kyoung Sub; Park, Sang Yoong; Lee, Seung-Cheol; Lee, Jong-Hwan; Chung, Chan Jong; Choi, So Ron (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
CHARGE syndrome is a rare genetic disorder with CHD7 gene mutation. CHARGE is an acronym for coloboma (C), heart disease (H), atresia of choanae (A), retardation of growth (R), genitourinary malformation (G), and ear abnormalities (E). Patients with CHARGE syndrome need to undergo many surgeries due to their various congenital anomalies. Since airway abnormalities frequently accompany CHARGE syndrome, general anesthesia remains a challenge. Here we report a case of difficult intubation in a 35-month-old boy with CHARGE syndrome during general anesthesia and the experience of successful intubation using D-blade of C-MAC® video laryngoscope. KCI Citation Count: 0